Return to work after primary total hip arthroplasty: a nationwide cohort study - Laasik, Raul; Lankinen, Petteri; Kivimäki, Mika; Aalto, Ville; Saltychev, Mikhail; Mäkelä, Keijo; Vahtera, Jussi (Acta Orthopaedica, 2019)
Background and purpose — While the number of working-age patients undergoing total hip arthroplasty (THA) is increasing, the effect of the surgery on patients’ return to work (RTW) is not thoroughly studied. We aimed to identify risk factors of RTW after THA among factors related to demographic variables, general health, health risk behaviors, and socioeconomic status. Patients and methods — We studied 408 employees from the Finnish Public Sector (FPS) cohort (mean age 54 years, 73% women) who underwent THA. Information on demographic and socioeconomic variables, preceding health, and health-risk behaviors was derived from linkage to national health registers and FPS surveys before the operation. The likelihood of return to work was examined using Cox proportional hazard modeling. Results — 94% of the patients returned to work after THA on average after 3 months (10 days to 1 year) of sickness absence. The observed risk factors of successful return to work were: having < 30 sick leave days during the last year (HR 1.8; 95% CI 1.4–2.3); higher occupational position (HR 2.2; CI 1.6–2.9); and BMI < 30 (HR 1.4; CI 1.1–1.7). Age, sex, preceding health status, and health-risk behaviors were not correlated with RTW after the surgery. Interpretation — Most employees return to work after total hip arthroplasty. Obese manual workers with prolonged sick leave before the total hip replacement were at increased risk of not returning to work after the surgery.